COVID-19 전후 국가R&D 연구성과 영향 요인 비교분석 - 의약학분야와 전체 분야의 차별성을 중심으로 - 차윤경(Yun-kyung Cha); 이홍석(HongSeok Lee); 허광래(Kwang-Lae Hoe) (한국콘텐츠학회 논문지, 23(12), 2023)
본 연구는 COVID-19 팬데믹 전후로 국가연구개발사업의 연구성과 영향 요인을 비교분석하여 위기 상황에서 적용 가능한 정책적 시사점을 도출하는 것을 목적으로 하고 있다. 특히 기초연구사업의 의약학분야와 전체 분야를 함께 분석함으로써 차별성을 도출하여 의약학분야만의 특성을 세밀하게 파악하고자 하였다. 연구성과 영향 요인은 성별, 과제별 유형(개인연구/집단연구), 정부출연금의 3가지로 추출하였고, SCI(E)(Science Citation Index Expanded)논문 성과의 양적차이에 영향을 미쳤는지를 분석하였다. 실증 분석결과 성별은 기초연구사업 의약학분야에서 COVID-19 발생 전후로 SCI(E)논문 성과에 영향을 미치지 않는 반면, 전체 분야에서는 남성 연구책임자가 SCI(E)논문 성과 도출에 상대적으로 높은 영향을 미친 것으로 나타났다. 또한 과제별 유형 중에서는 집단연구가 의약학분야 SCI(E)논문 성과 도출에 상대적으로 높은 영향을 미쳤으며 전체 분야에서는 COVID-19 발생 전후로 편차가 있는 것으로 분석되었다. 이러한 분석결과는 COVID-19와 같은 위기를 대비하여 학문분야별로 이끌어 갈 정책방향을 차별화하여야 함을 시사한다. The purpose of this study is to compare and analyze the factors influencing the research achievement of national R&D projects before and after the COVID-19 pandemic, and to derive policy implications applicable to crisis situations. The subjects of my research are Medical sciences field of the Basic Research Program, and by analyzing the entire field together, I tried to look at the characteristics of the fields of medicine and pharmacy in detail. As a result, it was found that gender did not affect the performance of SCI(E) publication before and after the outbreak of COVID-19 in the field of Medical sciences, while male principal investigators had a relatively high influence on the performance of SCI(E) publication in all fields. In addition, among the types, group studies had a relatively high impact on the outcomes of SCI(E) publication in the field of Medical sciences, and it was analyzed that there were deviations before and after the outbreak of COVID-19 in the overall field. The results of this analysis suggest that in preparation for crises such as COVID-19, it is necessary to differentiate the policy direction to be led by each academic field. KCI Citation Count: 0